ANALYSIS OF RICE MARKETING EFFICIENCY THROUGH THE STRUCTURE CONDUCT PERFORMANCE APPROACH - Adzim, Fauzul; Rachmadi, Moch Faizal (Universitas Negeri Semarang, 2025)
This study aims to analyze the efficiency of rice marketing in Ngawi Regency. This study uses the Structure-Conduct-Performance (SCP) method to analyze the efficiency of rice marketing. The data collection methods involved surveys and structured interviews with actors in the rice distribution chain. The snowball sampling method is used in this study to follow the marketing flow from farmers to end consumers. The study's results indicate that five main distribution channel patterns were identified. Each actor in the distribution chain has different contributions to marketing activities, including exchange functions, physical functions, and facility functions. The Farmer's Share value in each rice marketing channel in Ngawi Regency shows the proportion of price acceptance received by farmers compared to the price paid by end consumers. The analysis of five rice marketing channels in Ngawi Regency shows that channel 2 has the highest Farmer’s Share (54.62%), while channel 5 is the most cost-efficient with a π/c ratio 1.32. This study contributes to agricultural marketing studies by highlighting the importance of evaluating distribution channels based on the balance between the value received by producers and cost efficiency.